From cumulative cultural transmission to evidence-based medicine: evolution of medicinal plant knowledge in Southern Italy - Leonti, Marco; Staub, Peter O.; Cabras, Stefano; Castellanos, Maria Eugenia; Casu, Laura (Frontiers in Pharmacology, 2015)
In Mediterranean cultures written records of medicinal plant use have a long tradition. This written record contributed to building a consensus about what was perceived to be an efficacious pharmacopoeia. Passed down through millennia, these scripts have transmitted knowledge about plant uses, with high fidelity, to scholars and laypersons alike. Herbal medicine’s importance and the long-standing written record call for a better understanding of the mechanisms influencing the transmission of contemporary medicinal plant knowledge. Here we contextualize herbal medicine within evolutionary medicine and cultural evolution. Cumulative knowledge transmission is approached by estimating the causal effect of two seminal scripts about materia medica written by Dioscorides and Galen, two classical Greco-Roman physicians, on today’s medicinal plant use in the Southern Italian regions of Campania, Sardinia and Sicily. Plant-use combinations are treated as transmissible cultural traits (or “memes”), which in analogy to the biological evolution of genetic traits, are subjected to mutation and selection. Our results suggest that until today ancient scripts have exerted a strong influence on the use of herbal medicine. We conclude that the repeated empirical testing and scientific study of health care claims is guiding and shaping the selection of efficacious treatments and evidence-based herbal medicine.